The effect of intellectual intelligence and adversity quotient on learning motivation - Samsilayurni Samsilayurni; Gunawan Ismail; Nipriansyah Nipriansyah; Edy Susanto; Elsa Viona (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2021)
The purpose of this study was to analyze the effect of intellectual intelligence and Adversity Quotient on learning motivation State Vocational High School 1 Pasmah Air Keruh. The sample in this study amounted to 96 students. The instrument used in this study was a questionnaire or questionnaire. The data analysis technique used in this research is inferential statistical analysis, correlation test, T test and F test. Based on the results of the study, there is a significant influence of intellectual intelligence and adversity quotient together on learning motivation. This means that the higher the level of intellectual intelligence and adversity quotient in students, the more motivating and enthusiastic students are in learning